Changes in South Atlantic Cyclones due Climate Change - Gramcianinov, Carolina Barnez (2018)
Cyclones distribution and intensities impact directly on human activities, mainly due to their associated intense precipitation and winds. The main aim of this thesis is to understand changes in the cyclones originated in the South Atlantic focusing on their genesis and intensifying mechanisms. Cyclones are identified and tracked based on the relative vorticity field at 850 hPa computed from the winds. The characteristics of the cyclones are obtained by diagnostic variables sampled within a radial distance from each cyclone center and to produce a spatial distribution of the cyclone properties at the time of genesis. Also, cyclone centered composites are used to analyze the cyclone structure and the evolution of cyclones during their genesis. The climatology of cyclones was done using NCEP-CFSR and shows four main cyclogenesis regions in the South Atlantic Ocean: on the Southern Brazilian coast (SE-BR, 30°S), over the continent near the La Plata river discharge region (LA PLATA, 35°S), on the southeastern coast of Argentina (ARG, 40°S-55°S) and on the Southeastern Atlantic (SE-SAO, centered at 55°S and 10°W). To access changes in cyclone development, we used the CMIP5 HadGEM2-ES historical experiment (1980-2005) and RCP8.5 future projection (2074-2099). The HadGEM2-ES can represent the main South Atlantic characteristics of cyclones according to NCEP-CFSR climatology. However, there is an underestimation in cyclone frequency in the equatorward side of the storm track, particularly in the LA PLATA region. The HadGEM2-ES RCP8.5 future projection shows a general decrease of approximately 10% of cyclogenesis in the South Atlantic domain, which is mainly related to the poleward shift of the storm track. However, LA PLATA region presents a slight increase in its cyclogenetic activity (6.1 and 3.6%), in the summer and winter, respectively). The increase in genesis at 30°S over the continent is associated with the strengthening of the upper-level jet and the increase of warm and moisture advections at the same location. The enhance in the moisture transport from the tropics is also related to the intensification of the cyclone in the domain, mainly northward of 35°S. Finally, a downscaling using WRF was performed in an attempt to improve the climate model resolution. However the downscaling produces less and weaker cyclones in the NCEP-CFSR and HadGEM2-ES runs. The only region that presented an improvement was LA PLATA, due to the better representation of local features related to orography and moisture processes. The downscaled HadGEM2-ES RCP8.5 also shows an increase in cyclogenesis in the LA PLATA region and other locations. The HadGEM2-ES RCP8.5 projection and its downscaling shows that the cyclogenesis in some locations of South America is increasing, mainly due to the increase in the low-level moisture content and the strengthening of the equatorward flank of the upper-level jet. The cyclones in this locations will be slightly intense (between 20°S and 30°S) and will affect a narrow area close to the South American coast.